PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR PADA MATERI ENERGI DAN PERUBAHANNYA - Della Meidina Fortuna (STKIP Subang, 2023)
Based on the results of observations carried out in class III of SD Negeri Cimayang 01, Pamijahan District, Bogor Regency, for the 2023/2024 academic year, information was obtained that the learning process carried out was still teacher-oriented (Teacher Centered) and had not obtained optimal results. Students tend to be passive, tend to chat with their friends, are not able to express opinions and have no desire to ask questions. Meanwhile, the teacher in the learning process only uses the Direct Instruction (Lecture) learning model. The aim of this research is to determine the effect of the Problem Based Learning (PBL) model on learning outcomes in the material Energy and its Changes. This research method uses quasi-experimental research. Experimental research is defined as a research method used to find the effect of certain treatments on others under controlled conditions. This research was conducted three times in each class group. Sampling was carried out using a cluster random sampling technique, namely class IIIA (as Experiment Class) and class IIIB (as Control Class) with a total of 40 students. Data collection techniques used test, documentation and observation techniques. Research data was collected using an initial ability test (pretest) and final ability test (posttest). Based on the results of the N-Gain calculation in the experimental class, an average value of 58.03 (medium category) was obtained, which means that the implementation of learning was quite effective. Meanwhile, in the control class, an average score of 49.93 (medium category) was obtained, which means learning was quite effective. Based on the results of this research, it can be concluded that the problem based learning model has an influence on learning outcomes regarding Energy and its Changes. This is shown by the value of tcount = 0.0339 while ttable = 0.05 with db 40. Thus it is known that tcount <ttable, namely 0.0339 <0.05, which means Ha is accepted and Ho is rejected. This shows that there is a significant influence of the use of the problem based learning model on the learning outcomes of the Energy and Changes material for class III of SD Negeri Cimayang 01 Pamijahan, Bogor Regency, Academic Year 2023/2024.